Secondary renal amyloidosis in a patient of pulmonary tuberculosis and common variable immunodeficiency - Balwani Manish R; Kute Vivek B; Shah Pankaj R; Wakhare Pawan; Trivedi Hargovind L (Society of Diabetic Nephropathy Prevention, 2015)
Common variable immunodeficiency (CVID) usually manifests in the second or third decade of life with recurrent bacterial infections and hypoglobulinemia. Secondary renal amyloidosis with history of pulmonary tuberculosis is rare in CVID, although T cell dysfunction has been reported in few CVID patients. A 40-year-old male was admitted to our hospital with a 3-month history of recurrent respiratory infections and persistent pitting pedal edema. His past history revealed 3 to 5 episodes of recurrent respiratory tract infections and diarrhoea each year since last 20 years. He had been successfully treated for sputum positive pulmonary tuberculosis 8 years back. Laboratory studies disclosed high erythrocyte sedimentation rate (ESR), hypoalbuminemia and nephrotic range proteinuria. Serum immunoglobulin levels were low. CD4/CD8 ratio and CD3 level was normal. C3 and C4 complement levels were normal. Biopsy revealed amyloid A (AA) positive secondary renal amyloidosis. Glomeruli showed variable widening of mesangial regions with deposition of periodic schiff stain (PAS) pale positive of pink matrix showing apple green birefringence on Congo-red staining. Immunohistochemistry was AA stain positive. Immunofluorescence microscopy revealed no staining with anti-human IgG, IgM, IgA, C3, C1q, kappa and lambda light chains antisera. Patient was treated symptomatically for respiratory tract infection and was discharged with low dose angiotensin receptor blocker. An old treated tuberculosis and chronic inflammation due to recurrent respiratory tract infections were thought to be responsible for AA amyloidosis. Thus pulmonary tuberculosis should be considered in differential diagnosis of secondary causes of AA renal amyloidosis in patients of CVID especially in endemic settings.